2001
DOI: 10.1038/sj.ijo.0801566
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type dependent upregulation of human skeletal muscle UCP2 and UCP3 mRNA expression by high-fat diet

Abstract: OBJECTIVE:To test the hypothesis that consumption of a high-fat diet leads to an increase in UCP mRNA expression in human skeletal muscle. In a group of endurance athletes, with a range in ®ber type distribution, we hypothesized that the effect of the high-fat diet on UCP2 and UCP3 mRNA expression is more pronounced in muscle ®bers which are known to have a high capacity to shift from carbohydrate to fat oxidation (type IIA ®bers). DESIGN: Ten healthy trained athletes (®ve males, ®ve females) consumed a low-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 40 publications
11
63
1
Order By: Relevance
“…Enhanced expression of UCPs after high fat diet feeding is well known and may be related to an increased need to handle lipids as a fuel substrate under this condition. Up-regulation of muscle UCP3 mRNA levels by high fat diet was previously reported both in humans 47 and rodents, 15,17 although results are conflicting; 16 we confirmed this effect of high fat diet on muscle UCP3 both at the mRNA and the protein level. We also found increased levels of the mRNAs for all three UCPs in the BAT of high fat diet-fed B6 mice: previous reports in this strain found BAT UCP1 mRNA levels already increased 16 but BAT UCP2 and UCP3 mRNA levels unchanged 15,16 after experimental periods shorter than the one used by us (2 or 8 weeks vs 18 weeks).…”
Section: Ucp3 and Vitamin Asupporting
confidence: 78%
See 1 more Smart Citation
“…Enhanced expression of UCPs after high fat diet feeding is well known and may be related to an increased need to handle lipids as a fuel substrate under this condition. Up-regulation of muscle UCP3 mRNA levels by high fat diet was previously reported both in humans 47 and rodents, 15,17 although results are conflicting; 16 we confirmed this effect of high fat diet on muscle UCP3 both at the mRNA and the protein level. We also found increased levels of the mRNAs for all three UCPs in the BAT of high fat diet-fed B6 mice: previous reports in this strain found BAT UCP1 mRNA levels already increased 16 but BAT UCP2 and UCP3 mRNA levels unchanged 15,16 after experimental periods shorter than the one used by us (2 or 8 weeks vs 18 weeks).…”
Section: Ucp3 and Vitamin Asupporting
confidence: 78%
“…In fact, studies in humans under high fat diets showed increases of fat oxidation and UCP3 expression in muscle that were not accompanied by increases of circulating NEFA levels. 47,51 Lower levels of adipose leptin mRNA in B6 mice fed vitamin A-supplemented diets is in agreement with downregulation of adipose leptin mRNA levels following acute RA-treatment in rats and mice 27,28 and reduction of circulating leptin levels following dietary vitamin A supplementation in rats. 30 Our results further suggest that retinoids may by themselves exert an inhibitory effect on leptin expression that is not secondary to a reduction of fat content, because the depressed adipose leptin mRNA levels found did not correlate with comparable reductions of the adipose depots mass.…”
Section: Ucp3 and Vitamin Amentioning
confidence: 53%
“…This reevaluation presented in Table 4 constituted the backbone of the proposal that the primary function of UCP1-homologues in the skeletal muscle and BAT may somehow be involved actively or passively with the regulation of lipids as fuel substrate rather than in the mediation of thermogenesis [69]. This contention has since been reinforced by numerous data in animals and in humans, the most compelling of which are that (i) changes in UCP2 and UCP3 gene expressions during fasting, in parallel to key regulators of lipid oxidation, are more pronounced in white muscles (predominantly fast glycolytic) than in red muscles (predominantly slow oxidative) and hence consistent with the greater dependency of slowoxidative muscles on lipids as fuel substrate, and the greater shift between glucose and lipids as fuel substrate in fastglycolytic muscles during fasting [69,72,73], and that (ii) an increase in dietary fat leads to consistent elevations in UCP2 and UCP3 expressions in skeletal muscle and several other organs/tissues [67,68,74,75]. Furthermore, the associations found in humans between polymorphism in UCP2 or UCP3 with significant reductions in lipid oxidation [37][38][39] and that the short-insert isoform of UCP5/BMCP1 is correlated with lipid oxidation during physiological insulin infusion [76], are consistent with the proposal of a role for UCP1-homologues in the regulation of lipids as fuel substrate.…”
Section: Ucp1-homologues: a Link With Regulation Of Lipids As Fuel Sumentioning
confidence: 99%
“…Indeed, a high turnover rate of IMCL is considered to inhibit accumulation of toxic fatty acid metabolites such as diacylglycerol (DAG), peroxidised fatty acids and ceramides, which are supposed to interfere with insulin signaling (9,(12)(13)(14). Along this line, some of us have previously hypothesized that uncoupling protein-3 (UCP3), a mitochondrial anion carrier protein which is highly expressed in muscle cells, acts as a mitochondrial export protein for fatty acid anions and/or lipid peroxides, and via this mechanism it prevents mitochondrial oxidative damage and resulting deterioration of insulin efficiency (15)(16)(17)(18). Support for such hypothesis comes from studies showing that the UCP3 gene expression is consistently upregulated in various conditions of stimulated energy provision by fat oxidation (16,(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, some of us have previously hypothesized that uncoupling protein-3 (UCP3), a mitochondrial anion carrier protein which is highly expressed in muscle cells, acts as a mitochondrial export protein for fatty acid anions and/or lipid peroxides, and via this mechanism it prevents mitochondrial oxidative damage and resulting deterioration of insulin efficiency (15)(16)(17)(18). Support for such hypothesis comes from studies showing that the UCP3 gene expression is consistently upregulated in various conditions of stimulated energy provision by fat oxidation (16,(19)(20)(21)(22)(23)(24)(25). Accordingly, insulin-resistant individuals already in a pre-diabetic state exhibit abnormal oxidative damage in muscle cells, as well as elevated intramitochondrial FFA accumulation together with lower UCP3 protein content (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%